The Influence of Working Capital Management, Market Risk, and Investment Strategy on Profitability With Financial Distress As an Intervening Variable (Study on Companies With Special Notations Listed on The Indonesia Stock Exchange For The 2019-2023 Perio - Susana K. Alfons; Valdo Hana Primasatria; Siti Mujanah; Achmad Yanu Alif Fianto (Journal of Social Research, 2025)
This study aims to examine the influence of working capital management, market risk, and investment strategy on profitability, with financial distress as an intervening variable. The research is conducted on companies with special notations listed on the Indonesia Stock Exchange (IDX) during the period of 2019-2023. Quantitative Research Methods The research uses quantitative analysis with an associative quantitative approach, which is research that asks about the relationship between two or more variables. The analysis is carried out using a quantitative approach with Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM-PLS) through Smart PLS 4.0 software. The results show that working capital management and investment strategy have a positive and significant impact on profitability, while market risk and financial distress negatively affect profitability. Furthermore, financial distress plays a significant mediating role between the independent variables and profitability. The model demonstrates a strong predictive ability with an R² value of 0.65 for profitability and 0.57 for financial distress. These findings suggest that efficient working capital management and appropriate investment strategies contribute to higher profitability, while market risks and financial distress pose a threat to the financial stability of companies.